In Vitro Method To Study Antifungal Perfusion in Candida Biofilms - Samaranayake, Y. H. (American Society for Microbiology, 2005)
Antimycotic perfusion through Candida biofilms was demonstrated by a modification of a simple in vitro diffusion cell bioassay system. Using this model, the perfusion of three commonly used antifungal agents, amphotericin B, fluconazole, and flucytosine, was investigated in biofilms of three different Candida species (i.e., Candida albicans, Candida parapsilosis, and Candida krusei) that were developed on microporous filters. Scanning electron microscopy revealed that C. albicans formed a contiguous biofilm with tightly packed blastospores and occasional hyphae compared with C. parapsilosis and C. krusei, which developed confluent biofilms displaying structural heterogeneity and a lesser cell density, after 48 h of incubation on nutrient agar. Minor structural changes were also perceptible on the superficial layers of the biofilm after antifungal perfusion. The transport of antifungals to the distal biofilm-substratum interface was most impeded by C. albicans biofilms in comparison to C. parapsilosis and C. krusei. Fluconazole and flucytosine demonstrated similar levels of perfusion, while amphotericin B was the least penetrant through all three biofilms, although the latter appeared to cause the most structural damage to the superficial cells of the biofilm compared with the other antifungals. These results suggest that the antifungal perfusion through biofilm mode of growth in Candida is dependent both on the antimycotic and the Candida species in question, and in clinical terms, these phenomena could contribute to the failure of Candida biofilm-associated infections. Finally, the in vitro model we have described should serve as a useful system to investigate the complex interactions that appear to operate in vivo within the biofilm-antifungal interphase.